Variations in tree community composition and structure in a fragment of tropical semideciduous forest in southeastern Brazil related to different human disturbance histories - Toniato, MTZ; de Oliveira-Filho, A. T. (Elsevier B.V., 2004)
In an area of tropical seasonal semideciduous forest, the soil characteristics, floristic composition, physiognomic structure, and the distribution of three regeneration and three dispersal guilds were studied for four stands within the forest that had documented histories of varying degrees of human disturbance. The aim was to study forest regeneration in areas of preserved forest and secondary forest, with parts of both types of forest experiencing either 'intensive' or 'occasional' cattle trampling. The study was carried out in the Sebastiao Aleixo da Silva Ecological Station, Bauru, São Paulo State, Brazil. Two stands were called 'secondary' because they corresponded to forest tracts that were felled and occupied by crops and pastures in the past and then abandoned to forest regeneration ca. 40 years before this study. The other two stands, called 'preserved', corresponded to areas of the fragment where the forest has been maintained with only minor human impacts. The arboreal component of the tree community (diameter at breast height or dbh greater than or equal to 5 cm) was sampled in 20 plots of 40 m x 40 m, and the subarboreal component (diameter at the base of the stem or dbs < 5 cm and height greater than or equal to 0.5 m) in subplots of 40 m x 2 m. Physiognomic features, such as canopy height and density of climbing plants, were registered all over a 5 m x 5 m gridline laid on the sample plots. Soil bulk samples were collected for chemical and textural analyses. Most detected differences contrasted the secondary to the preserved forest stands. The soils of the secondary stands showed higher proportions of sand and lower levels of mineral nutrients and organic matter than those of the preserved stands, probably due to higher losses by leaching and erosion. Compared to the secondary stands, the preserved ones had higher proportions of tall trees, higher mean canopy height, lower species diversity, higher abundance of autochorous and shade-tolerant climax species, and lower abundance of pioneer and light-demanding climax species. Despite the high proportion of species shared by the preserved and secondary stands (108 out of 139), they differed consistently in terms of density of the most abundant species. on the other hand, the secondary and preserved stands held similar values for tree density and basal area, suggesting that 40 years were enough to restore these features. Effects of cattle trampling on the vegetation were detected for the frequency of trees of anemochorous and zoochorous species, which were higher in the stands under occasional and intensive cattle trampling, respectively. The density of thin climbers was lower in the stands with intensive trampling. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Brazil; forest disturbance; forest fragments; forest regeneration; regeneration guilds; dispersal guilds; tropical semideciduous forest